Maximizing the Utilization of School Based Assessment to Enhance Teaching and Learning Experience in Science Subjects - Nwafor, Stephen Chinedu; Fabunmi, Boboye Joshua; Mbaegbu, Chioma Stephanie (Universitas Islam Negeri Walisongo Semarang, 2024)
The successful implementation of school based assessment has recorded positive influence on teaching and learning process in developed countries of the world. However, among the developing countries like Nigeria, there seem to be a lot of challenges. Hence, the purpose of study was to determine the extent school based assessment influence the teaching and learning experience in science subjects in Anambra State, Nigeria and the challenges encountered in the process. The investigation was conducted using a descriptive survey design. The study made use of mean and standard deviation for data analysis. The findings of the study revealed that school based assessment influences the teaching and learning of science subjects to a high extent. Moreover, the use of unprofessional teachers, inadequate teachers/students motivation and lack of unwillingness by the students to take part in school based assessment are some of the problems facing the successful implementation of school based assessment while adequate motivation of the teachers, employment of trained teachers and organizing conferences and seminars to train the teachers on school based assessment guidelines among others were proffered as the solutions to eradicate these challenges.